Peningkatan Citra Desa dan Penguatan Pendidikan Karakter Melalui Literasi dan Sosialisasi Anti-Bullying di Desa Simpang Tiga Daratan - Jumili Arianto; Hamad Alfarizi; Diana Gustia; Muzaffar Mohan; Marsha Fanni; Jumadi Maulana Yoga; Desmiyati Syafitri; Nurjannah Nurjannah; Yunia Afrioni Wulandari; M. Alvin Ramadhan; Zhinda Lestary (Lembaga Pengembangan Kinerja Dosen, 2024)
Real Work Lectures (KKN) is a community service program that students must take part in as part of the higher education curriculum in Indonesia. The aim of this activity is to develop students' abilities to apply the knowledge and skills they have acquired during lectures in real contexts in society. KKN activities were carried out in Simpang Tiga Daratan village, Enok District, Indragiri Hilir Regency for 40 days, with a focus on the Literacy Work Program in the form of the Anti-Bully movement. The methods used include counseling and training. The results of this activity show an increase in public awareness about the importance of bullying prevention, as well as the existence of sustainable programs that can be implemented by the community independently. This activity also provides direct experience for students in interacting and contributing to society. In conclusion, KKN is an important means for students to apply academic knowledge in everyday life and have a positive impact on the local community.